Stakeholder feedback on ecological benefits at dredged material placement sites - Littles, Chanda J.; Russ, Emily R.; Lemasson, Bertrand H.; Schultz, Martin T.; Tidwell, Kyle S.; Moritz, Hans R.; Carroll, Sean T. (Frontiers in Ecology and Evolution, 2025)
We adopted a matrix framework to evaluate potential ecological benefits at beneficial use of dredged material (BUDM) placement sites. Monitoring protocols developed in California (U.S.A.) were adapted to solicit feedback on ecosystem functions and indicators most relevant for BUDM applications. We present feedback received in the context of estuaries and a large coastal river in the Pacific Northwest of the United States, though methods are easily transferable. Through a series of workshops, stakeholders were asked to identify and prioritize functions and indicators they deemed most applicable to BUDM assessment. From a stakeholder group of over 50 invitees representing 21 organizations, we received matrices from just under half (n=9). Matrix input often reflected collaborative feedback from multiple individuals within a single organization. Top ecosystem functions identified were support for protected species, sea level rise amelioration, nursery habitat, support for vascular plants, and nekton habitat. Top indicators selected for assessing those functions were the marsh vegetation, benthic infauna, water quality, distribution of submerged vegetation and macroalgae, and the marshplain elevation. Not all indicators were applicable to selected functions and there was high variability in the indicator prioritization. A final stakeholder workshop was held to discuss results and participants expressed support for monitoring indicators (e.g., biomass) with the greatest potential to capture changes in benefits across multiple ecological functions and over time. We demonstrate a process to facilitate ongoing stakeholder collaboration to proactively plan for evaluating ecological priorities and selecting relevant indicators that enable users to effectively monitor and quantify BUDM benefits.